2005
DOI: 10.1039/b502350e
|View full text |Cite
|
Sign up to set email alerts
|

The role of Oad in the decomposition of NH3 adsorbed on Ir(110): a combined TPD and high-energy resolution fast XPS study

Abstract: High energy resolution fast XPS combined with TPD experiments were used to study the effect of chemisorbed oxygen on the adsorption and dissociation of NH(3) on Ir(110). Below 250 K the presence of O(ad) does not influence NH(3) decomposition. Above 250 K O(ad) enhances NH(3) dissociation, which results in three times as much N(2) formation and less molecular NH(3) desorption compared to the experiments without O(ad). The effect of O(ad) can be attributed to destabilization of NH(ad) on the surface, resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
(42 reference statements)
0
9
1
Order By: Relevance
“…Meanwhile, ammonia is a toxic component in the waste stream that can cause pollution of lakes and seas, and its release in the environment is unwanted. Owing to its great industrial importance and air pollution control, the surface chemistry of ammonia has attracted much attention. There are a great number of studies for ammonia dissociation into N 2 and H 2 , or oxidation toward N 2 and H 2 O on a variety of transition metal surfaces. It is observed that the oxidation of ammonia can lead to formation of possible nitrogenous byproducts NO x besides N 2 , depending on reaction conditions such as the catalyst, experimental pressure (different ratios of NH 3 /O 2 ), and temperature. ,, , In general, high-temperature and oxygen-rich conditions favor NO x formation, whereas low-temperature and oxygen-lean conditions favor N 2 formation.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, ammonia is a toxic component in the waste stream that can cause pollution of lakes and seas, and its release in the environment is unwanted. Owing to its great industrial importance and air pollution control, the surface chemistry of ammonia has attracted much attention. There are a great number of studies for ammonia dissociation into N 2 and H 2 , or oxidation toward N 2 and H 2 O on a variety of transition metal surfaces. It is observed that the oxidation of ammonia can lead to formation of possible nitrogenous byproducts NO x besides N 2 , depending on reaction conditions such as the catalyst, experimental pressure (different ratios of NH 3 /O 2 ), and temperature. ,, , In general, high-temperature and oxygen-rich conditions favor NO x formation, whereas low-temperature and oxygen-lean conditions favor N 2 formation.…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia oxidation over Ir(110) 90 and Ir(111) 91 has also been probed by TP-XPS. NH 3 readily reacts over Ir (110) to form NH a between 225-300 K. This in turn decomposes to atomic nitrogen B400 K, with recombinative N 2 desorption at 650 K. In contrast, NH 3 does not decompose over clean Ir (111).…”
Section: Nh 3 Oxidationmentioning
confidence: 99%
“…It is observed that the oxidation of ammonia can lead to formation of possible nitrogenous byproducts NO x besides N 2 , depending on reaction conditions such as the catalyst, experimental pressure (different ratios of NH 3 /O 2 ), and temperature. 22,23,[27][28][29][30][31][32]35 In general, high-temperature and oxygen-rich conditions favor NO x formation, whereas lowtemperature and oxygen-lean conditions favor N 2 formation. The key problem in the ammonia reduction is how to effectively improve the N 2 formation route and selectively avoid the conversion of nitrogen into its oxides.…”
Section: Introductionmentioning
confidence: 99%
“…Ir-based catalysts were found to possess high low-temperature oxidation activity and more selectivity toward nitrogen than platinum and some other metals. 24,26,[28][29][30][31][32]37 Several fundamental studies concerning ammonia decomposition and oxidation on various iridium single surfaces such as Ir(110), 10,29−32 Ir(510), 32 and Ir(111) 28,29 have been performed. It is found that these iridium single surfaces were effective for the selective reduction of NH 3 toward N 2 , but with a small amount of NO x .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation